BIG3 inhibits insulin granule biogenesis and insulin secretion. (7th April 2014) - Li, Hongyu; Wei, Shunhui; Cheng, Kenneth; Gounko, Natalia V; Ericksen, Russell E; Xu, Aimin; Hong, Wanjin; Han, Weiping
Abstract While molecular regulation of insulin granule exocytosis is relatively well understood, insulin granule biogenesis and maturation and its influence on glucose homeostasis are relatively unclear. Here, we identify a novel protein highly expressed in insulin‐secreting cells and name it BIG3 due to its similarity to BIG/GBF of the Arf‐GTP exchange factor (GEF) family. BIG3 is predominantly localized to insulin‐ and clathrin‐positive trans‐Golgi network (TGN) compartments. BIG3‐deficient insulin‐secreting cells display increased insulin content and granule number and elevated insulin secretion upon stimulation. Moreover, BIG3 deficiency results in faster processing of proinsulin to insulin and chromogranin A to β‐granin in β‐cells. BIG3‐knockout mice exhibit postprandial hyperinsulinemia, hyperglycemia, impaired glucose tolerance, and insulin resistance. Collectively, these results demonstrate that BIG3 negatively modulates insulin granule biogenesis and insulin secretion and participates in the regulation of systemic glucose homeostasis.